ANALISIS PRODUKTIVITAS MESIN DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) SEBAGAI DASAR PERBAIKAN MESIN PENGOLAHAN GARAM DI PT. X - Ilham Shandy Nugroho, (2023)
PT.X, a salt manufacturing company, faces issues with ineffective corrective maintenance on their machines, resulting in production delays and low machine effectiveness. The OEE (Overall Equipment Effectiveness) method is used to assess machine performance and identify correlations between variables and OEE values, as well as the dominant factors affecting OEE from independent variables. FMEA and cause-and-effect diagrams are utilized to pinpoint the primary causes of failures and provide recommendations for improvement. The research findings indicate an OEE value of 66,48%, below global standards. Downtime is identified as the variable with the most significant impact, accounting for 26% of the reduced OEE value. Recommendations include optimizing rest time, conducting regular meetings and briefings, implementing a machine checklist, establishing a maintenance schedule, assigning tasks for contaminant sorting, implementing regular maintenance schedules, and ensuring cleanliness through sweeping and mopping. Additionally, a financial comparison outcome adjustment from Rp. 154,600,000,- to Rp. 7,600,000, -.